Synergistic effect and mechanism of FeOx and CeOx co-doping on the superior catalytic performance and SO2 tolerance of Mn-Fe-Ce/ACN catalyst in low-temperature NH3-SCR of NOx. Issue 6 (December 2021) - Jiang, Lijun; Liang, Ya; Liu, Weizao; Wu, Hongli; Aldahri, Tahani; Carrero, Dennise Sosa; Liu, Qingcai
Abstract: Developing alternative NH3 -SCR catalysts with high SO2 tolerance is of great significance for NO x emission control at low temperature. For further improving the catalytic performance and SO2 tolerance of nitric acid modified activated carbon (ACN) loaded MnO x catalyst (Mn/ACN), FeO x and CeO x were co-doped by impregnation. FeO x and CeO x co-doped Mn-Fe(0.4)-Ce(0.4)/ACN exhibited improved catalytic activity, N2 selectivity, and SO2 tolerance. The NO x conversion of Mn-Fe(0.4)-Ce(0.4)/ACN was higher than 95% in 100–250 °C and remained around 91% after 32 h reaction under 100 ppm SO2 and 10 vol% H2 O at 175 °C. Co-doping FeO x and CeO x greatly enhanced the surface acidity, redox properties, and surface chemisorbed oxygen of Mn-Fe(0.4)-Ce(0.4)/ACN through the interaction among Mn n+, Fe n+, and Ce n+, resulting in significantly promoted NH3 -SCR performance. The stronger surface acidity and promoted catalytic activity effectively inhibited the adsorption of SO2 and the reaction between SO2 and adsorbed NH3, respectively. Meanwhile, the adsorbed SO2 was preferentially induced to react with CeO x, preventing MnO x and FeO x from being sulfated. Finally, the synergistic mechanism of FeO x and CeO x co-doping on better SO2 tolerance for Mn-Fe(0.4)-Ce(0.4)/ACN catalyst was proposed. Graphical Abstract: ga1 Highlights: Mn-Fe-Ce/ACN exhibited superior catalytic activity, N2 selectivity, and SO2 tolerance. FeO x and CeO x co-doping highly enhanced the redox properties and surface acidity. Promoted catalytic activity and stronger surface acidity inhibited the adsorption of SO2 . SO2 preferentially reacted with CeO x preventing MnO x and FeO x from being sulfated.